2021
DOI: 10.1111/njb.03171
|View full text |Cite
|
Sign up to set email alerts
|

Functional aspects of solanaceae trichomes in heavy metal detoxification

Abstract: Solanaceous plants are ubiquitous and are able to colonize degraded, abandoned and metal polluted habitats. Members of the family have evolved interesting extrinsic and intrinsic traits to combat the metal toxicity in multiple ways. Indumentum constituted mostly of trichome layer provides structural defense for both biotic stress (herbivory, oviposition, microbial pathogenesis) and abiotic stress (like drought, heat, freezing, photooxidation and UV radiation). Plants with heavy metal tolerance can accumulate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 157 publications
(167 reference statements)
0
5
0
1
Order By: Relevance
“…In many cases, however, the functional benefit of trichomes is not yet clear [ 121 ] and awaits clarification. For instance, as recently discussed, trichomes may be active in metal detoxication [ 102 , 122 ]. Clearly, trichomes offer a huge variety of functions and sophisticated relationships between structure and mechanism.…”
Section: The Leaf Surfacementioning
confidence: 99%
“…In many cases, however, the functional benefit of trichomes is not yet clear [ 121 ] and awaits clarification. For instance, as recently discussed, trichomes may be active in metal detoxication [ 102 , 122 ]. Clearly, trichomes offer a huge variety of functions and sophisticated relationships between structure and mechanism.…”
Section: The Leaf Surfacementioning
confidence: 99%
“…There have been several studies and observations based on fluorescence microscopy indicating that trichomes serve as entry points for pollutants, import them from other cell types and tissues, and contribute to their accumulation and/or dissipation. , However, the mechanisms are still not precise. Trichomes of the Solanaceae family accumulate heavy metals, and Arabidopsis thaliana trichomes contain high glutathione concentration, suggesting that trichomes may function as an efficient site of xenobiotic conjugation as a part of plant elemental defense detoxification strategy. , Moreover, Alves et al observed high PAH fluorescence as well as the detected high activity of enzymes related to PAHs conjugation and degradation, such as cytochrome P450 (CYP) reductase and glutathione S-transferase in glandular trichomes of Medicago sativa . Additionally, Cave-Radet et al suggested that in higher plants, detoxification of organic xenobiotics is likely to occur within specialized cells, such as trichomes and pavement cells in Arabidopsis and in the salt glands’ basal cells in Spartina species.…”
Section: Uptake and Translocation And The Fate Of Pahs In Plantsmentioning
confidence: 99%
“…Despite their minute size, plant trichomes, which are literally the first site of contact with many environmental factors, provide substantial ecological advantages. These hair-like structures help plants tolerate biotic and abiotic stresses by protecting against herbivorous insects and microorganisms, excessive ultraviolet light, heat, drought, and even heavy metals (Hülskamp, 2004; Wagner, 2004; Yang and Ye, 2013; Koul et al, 2021; Zhang et al, 2021). In particular, glandular trichomes are a critical defense mechanism against arthropod herbivores, which warrants the study of their development and biochemistry (Bar and Shtein, 2019).…”
Section: Introductionmentioning
confidence: 99%